MEANINGS ASSIGNED BY MEN REGARDING THE RELATIONSHIP BETWEEN SMOKING AND CANCER - Luana Valentim Monteiro; Ítalo Rodolfo Silva; Cleson Oliveira de Moura; Marcelle Miranda da Silva (Universidade Federal do Paraná, 2019)
Objective: To understand the meanings assigned by men to the habit of smoking and its risks related to the development of cancer. Method: Qualitative study conducted in a specialized health care institute in Rio de Janeiro, Brazil. Eighteen men, both smokers and former smokers, were interviewed from November 2015 to April 2016. The data was analyzed using thematic content analysis. Results: Lack of knowledge about the habit of smoking and the feeling of pleasure that it provides were found to be related to a higher probability of starting the habit. The meaning attributed by men to the relationship between smoking and the health-disease process was related to family history or their own vulnerability. However, a number of men did not feel prepared to quit smoking due to their physical and psycho-emotional dependence. Conclusion: Smoking cessation may require professional support. It is necessary to recognize the habit of smoking as a health problem, to want to quit smoking, and to identify personal motivational factors.